2020
DOI: 10.1177/2280800020975721
|View full text |Cite
|
Sign up to set email alerts
|

Influence of curing duration and mixing techniques of bulk fill resin composites on bi-axial flexural strength and degree of conversion

Abstract: Objectives: The aim was to assess the influence of polymerization duration, method and resin manipulation techniques on the biaxial flexural strength (BFS) and degree of conversion (DC) of bulk fill resin composites (BFRC). Methods: One hundred and eighty disc specimens were fabricated using MultiCore (MC) and Core-It (CI) bulk fill resin composite. Each material group, specimens were divided into nine subgroups based on curing methods (Light cure for 10 and 20 s; and auto-cure) and mixing techniques (first au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…It has been reported that an increase in the monomer’s degree of conversion improves the physical and mechanical properties of composite resins. 21 , 22 Preheating resin-based restorative materials can increase the monomer’s degree of conversion and increase the polymerization rate. An increase in the material’s temperature decreases its viscosity, increasing the motility of free radicals and propagation of polymer chains, which result in the completion of the polymerization reaction, formation of more double bonds, and increased cross-linking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that an increase in the monomer’s degree of conversion improves the physical and mechanical properties of composite resins. 21 , 22 Preheating resin-based restorative materials can increase the monomer’s degree of conversion and increase the polymerization rate. An increase in the material’s temperature decreases its viscosity, increasing the motility of free radicals and propagation of polymer chains, which result in the completion of the polymerization reaction, formation of more double bonds, and increased cross-linking.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that an increase in temperature might increase the monomer’s degree of conversion, 23 improving composite resins’ physical and mechanical properties. 21 , 22 …”
Section: Discussionmentioning
confidence: 99%
“…Group IV (n=10): Harmonize composite discs. Composite was packed in the mold with a spatula and the surface was covered with acetate strip and pressed by a glass slab to extrude the excess and achieve consistent surface finish (16,17). The specimens were light cured using (Wood pecker LED-B) light-curing device for 40 seconds following manufacturer's recommended curing time.…”
Section: Methodsmentioning
confidence: 99%
“…Specimens were immersed in distilled water at 37 ±1°C for 1 week prior to testing to simulate the clinical intraoral conditions. Measurements of diameter (2r3) and thickness (d) of the discs were taken (16,17). II.b) Biaxial Flexural Strength Test Ball-on-3-balls biaxial flexural strength test was applied in a universal testing machine (Instron 3345, England) (Figure 2).…”
Section: Methodsmentioning
confidence: 99%
“…It emphasises optimisation through design and not through many experiments and introduces the influence of uncontrollable factors into the experimental design [ 28 , 29 , 30 , 31 , 32 , 33 ]. The Taguchi method combines orthogonal experiments and analysis of variance (ANOVA) [ 34 , 35 , 36 , 37 , 38 , 39 ] to determine the best combination of controllable factors to reduce the impact of uncontrollable factors on system quality fluctuations. Furthermore, the signal-to-noise ratio (SNR) method is an interdisciplinary evaluation and prediction approach [ 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%